Level of ethics and integrity and internal audit capability: a comparison of two Malaysian public sector organizations - Asmawati, Sajari; Hasnah, Haron; Ishak, Ismail; Nur Ain Zakiah, Mohd Yusof; Roszaini, Haniffa (Penerbit Universiti Malaysia Pahang, 2018)
The main purpose of this paper is to explain the possible influence of internal audit capability on the level of ethics and integrity in Malaysian public sector organizations i.e., Federal Statutory Body (FSB) and State Statutory Body (SSB). An explanatory case study method is used to collect the data whereby semi structured interviews, informal conversations, questionnaire and document reviews are conducted. The level of ethics and integrity is measured based on the Corporate Integrity System Malaysia (CISM) dimensions while the level of internal audit capability is measured using the Internal Audit Capability Model (IACM). SSB scored higher with a score of 70.85% as compared to FSB with a score of 66.1% in CISM dimensions. Overall, a score of more than 50% indicates that both organizations are serious in initiating proper integrity mechanism to maintain the highest levels of transparency, integrity and professionalism in their daily activities and at their work place. However, in terms of IACM, FSB fared better with a score of 76%, with a capability level of 2 as compared to SSB with a score of 71% with a capability level of 1. Further in-depth study is highly recommended to get more insight on the findings.